Incumplimiento del protocolo Alerta Emilia frente a la desaparición de niños y adolescentes en Ecuador - Cumbicos Orellana, Adriana Stefania (2024)
The present curricular integration work entitled "Non-compliance with the Emilia Alert protocol regarding the disappearance of children and adolescents in Ecuador" addresses an urgent and serious problematic in the country: the persistence and increase of cases of disappearance of minors. Despite having a broad legal framework intended to protect their rights, these cases have not ceased; on the contrary, they have been increasing. The Emilia Alert protocol was created with the purpose of having a mechanism that guarantees a quick response by the authorities in cases of the disappearance of children and adolescents. However, despite its implementation, there are still significant delays in the search process, which entails devastating consequences, the most fatal being the death of the missing child. To address this problematic in an effective way, the recommendations of this study focus on actions such as; the continuous training of State officials in charge of executing this protocol, the massive dissemination of information by the National Police, the continuation of the study of similar investigations, and the consideration of reforming the Organic Integral Penal Code to impose sanctions on officials who fail to comply with their obligations and therefore the missing person results killed. These measures seek to establish a legal framework that ensures the protection of the rights of children and adolescents in Ecuador, guaranteeing that the Emilia Alert protocol will be fully complied with.